2016
DOI: 10.1093/mnras/stw1994
|View full text |Cite
|
Sign up to set email alerts
|

The origin of rotation profiles in star-forming clouds

Abstract: Angular momentum distribution and its redistribution are of crucial importance in the formation and evolution of circumstellar disks. Many molecular line observations toward young stellar objects indicate that radial distributions of the specific angular momentum j have a characteristic profile. In the inner region, typically R < ∼ 100 AU, the specific angular momenta distribute like j ∝ r 1/2 , indicating existence of rotationally supported disk. In outer regions, R > ∼ 5000 AU, j increases as the radius incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…Therefore, in the context of prestellar cores, a very high binding energy also prevents any return in the gas phase. The second efficient mechanism for populating the gas phase is the chemical desorption (or reactive desorption) (Takahashi & Williams 2000;Garrod et al 2007;Dulieu et al 2013). Here, the energy released during the formation of the molecule itself is the promoter of the desorption.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the context of prestellar cores, a very high binding energy also prevents any return in the gas phase. The second efficient mechanism for populating the gas phase is the chemical desorption (or reactive desorption) (Takahashi & Williams 2000;Garrod et al 2007;Dulieu et al 2013). Here, the energy released during the formation of the molecule itself is the promoter of the desorption.…”
Section: Discussionmentioning
confidence: 99%
“…Recent ALMA observations of the disc of the young star HL Tau (ALMA Partnership et al 2015) have revealed the presence of multiple gaps at mm wavelengths. These gaps may be carved either by planets (Dipierro et al 2015) or be due to other processes (Takahashi & Inutsuka 2014;Gonzalez et al 2015;Takahashi et al 2016b). HL Tau is an extremely young object (Greaves et al 2008) that shows signs of outflows in the form of jets and infall from its parent cloud.…”
Section: Introductionmentioning
confidence: 99%
“…Time dependences for the observed star position on the celestial sphere, radiation flux from the star, frequency of detected radiation, major and minor semiaxes of the lensed star image have been calculated and plotted. The detailed observation of such lensing requires a space interferometer such as the Russian Millimetron project.It is expected that the Event Horizon Telescope [1-8] will measure in the next three years the shape of shadow [9-17] of the supermassive black SgrA* hole at the center of the Galaxy, illuminated by either a hot background gas and stars [18][19][20][21][22] or an accretion disk [23][24][25][26][27][28][29]. A black hole at the center of giant elliptic galaxy M87 is another promising candidate for measuring the shape of black hole shadow.…”
mentioning
confidence: 99%
“…It is expected that the Event Horizon Telescope [1-8] will measure in the next three years the shape of shadow [9-17] of the supermassive black SgrA* hole at the center of the Galaxy, illuminated by either a hot background gas and stars [18][19][20][21][22] or an accretion disk [23][24][25][26][27][28][29]. A black hole at the center of giant elliptic galaxy M87 is another promising candidate for measuring the shape of black hole shadow.…”
mentioning
confidence: 99%